Germline cdh1 g212e missense variant: Combining clinical, in vitro and in vivo strategies to unravel disease Burden - Figueiredo, J (2021)
E-cadherin, encoded by CDH1, is an essential molecule for epithelial homeostasis, whose loss or aberrant expression results in disturbed cell–cell adhesion, increased cell invasion and metas-tasis. Carriers of CDH1 germline mutations have a high risk of developing diffuse gastric cancer and lobular breast cancer, associated with the cancer syndrome Hereditary Diffuse Gastric Cancer (HDGC). The ubiquitous availability of cancer panels has led to the identification of an increasing amount of “incidental” CDH1 genetic variants that pose a serious clinical challenge. This has sparked intensive research aiming at an accurate classification of the variants and consequent validation of their clinical relevance. The present study addressed the significance of a novel CDH1 variant, G212E, identified in an unusually large pedigree displaying strong aggregation of diffuse gastric cancer. We undertook a comprehensive pipeline encompassing family data, in silico predictions, in vitro assays and in vivo strategies, which validated the deleterious phenotype induced by this genetic alteration. In particular, we demonstrated that the G212E variant affects the stability and localization, as well as the adhesive and anti-invasive functions of E-cadherin, triggering epithelial disruption and disorganization. Our findings illustrate the clinical implication of a complementary approach for effective variant categorization and patient management.